The Devising Approach in Student Training - Elitsa Yovcheva; Viara Gyurova (Педагогически форум)
With the changes brought by the new millennium, educational institutions have been given a " social calling" to prepare young people for the challenges of the 21st century, developing their skills of creative individuals and helping them to continually self-develop and be active agents in their own lives and social expectations towards themselves. Social expectations in the 21st century are high for all professions and the people who perform them. This also applies to creators of works of art, such as theater productions and films. They are creators in the classical sense of the word. Their construction and improvement as such creators is possible as a result of a creative process, the basis of which are the dialogue and cooperation between the participants, characteristic of the very popular today in Bulgaria "pedagogy of cooperation" (also called "collaborative pedagogy") and "collaborative (devising) theater”. The purpose of the article is to show possible projections of the collaborative approach, more specifically, the devising approach in student training. The realization of this goal goes through the presentation of the specific features of the approach laid down in the foundations of the pedagogy of cooperation and devising theater, and the outline of the parameters and conditions for its effective application in the training of students - future actors and theater or cinema directors, as well as in the training of specialists in other humanities majors.